Production of Bio-Gel from Waste of Cassava and Maize - Asiru, W. B.; Raji, A. O.; Alausa, N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Bio-ethanol was produced using starch extracted from cassava peel and cellulose from Corn cobs using acid hydrolysis and yeast for fermentation while Bio-gel fuel was produced using a composition of bioethanol and gel from water and Carboxymethyl Cellulose (CMC) in ratio 80%, 20% by volume respectively. The average yield of bioethanol is 757.33ml for cassava peel and 595.56 for corn cobs from 3.55L and 3.35L of filtrates respectively. The properties of bio-ethanol produced from the two samples compared favorably with the commercial ethanol. The bio-gel fuel which is an alternative source for cooking can also support outdoor burning. The formulation is made from 100% recycle of agricultural wastes making it very economical. The research work will have considerable impacts on the vision of bio-economy launched by many African countries, which is to be achieved through the creation and growth of novel industries that generate and develop bio-based services and products. It will also support the local content initiative of Nigeria government. The success of the study has a great impact on the environment being a waste conversion study.